A Safe GDNF and GDNF/BDNF Controlled Delivery System Improves Migration in Human Retinal Pigment Epithelial Cells and Survival in Retinal Ganglion Cells: Potential Usefulness in Degenerative Retinal Pathologies - Alicia Arranz-Romera; Maria Hernandez; Patricia Checa-Casalengua; Alfredo Garcia-Layana; Irene T. Molina-Martinez; Sergio Recalde; Michael J. Young; Budd A. Tucker; Rocío Herrero-Vanrell; Patricia Fernandez-Robredo; Irene Bravo-Osuna (MDPI AG, 2021)
We assessed the sustained delivery effect of poly (lactic-co-glycolic) acid (PLGA)/vitamin E (VitE) microspheres (MSs) loaded with glial cell-derived neurotrophic factor (GDNF) alone (GDNF-MSs) or combined with brain-derived neurotrophic factor (BDNF; GDNF/BDNF-MSs) on migration of the human adult retinal pigment epithelial cell-line-19 (ARPE-19) cells, primate choroidal endothelial (RF/6A) cells, and the survival of isolated mouse retinal ganglion cells (RGCs). The morphology of the MSs, particle size, and encapsulation efficiencies of the active substances were evaluated. In vitro release, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) cell viability, terminal deoxynucleotidyl transferase (TdT) deoxyuridine dUTP nick-end labelling (TUNEL) apoptosis, functional wound healing migration (ARPE-19; migration), and (RF/6A; angiogenesis) assays were conducted. The safety of MS intravitreal injection was assessed using hematoxylin and eosin, neuronal nuclei (NeuN) immunolabeling, and TUNEL assays, and RGC in vitro survival was analyzed. MSs delivered GDNF and co-delivered GDNF/BDNF in a sustained manner over 77 days. The BDNF/GDNF combination increased RPE cell migration, whereas no effect was observed on RF/6A. MSs did not alter cell viability, apoptosis was absent in vitro, and RGCs survived in vitro for seven weeks. In mice, retinal toxicity and apoptosis was absent in histologic sections. This delivery strategy could be useful as a potential co-therapy in retinal degenerations and glaucoma, in line with future personalized long-term intravitreal treatment as different amounts (doses) of microparticles can be administered according to patients' needs.